2014
DOI: 10.1111/jace.13296
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Highly Efficient Method for Synthesis of Ce3+‐Activated Borogermanate Scintillating Glasses in Air

Abstract: Fast Ce3+ -activated borogermanate scintillating glasses with the density of 5.58-5.67 g/cm 3 were synthesized by melt quenching method in air atmosphere for the first time. The optical transmittance and X-ray absorption near edge spectroscopy results confirm that Ce 4+ ions can be effectively reduced to Ce 3+ ions by adding 0.31 mol% Si 3 N 4 as a strong reducing agent during glass synthesis. The luminescence behavior under both ultraviolet and X-ray excitations indicate that the proposed Ce 3+ -activated bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The above‐mentioned reduction conditions not only complicate the synthesis process of glass material, but also accordingly increase the production cost. Interestingly, some reducing agents such as Si 3 N 4 and SiC that exhibit intrinsic reduction nature, have been utilized to synthesize certain transparent and colorless glasses activated with cerium ions. This strategy seems to be more effective in borosilicate, borogermanate, and borate glass systems as reported in our previous work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above‐mentioned reduction conditions not only complicate the synthesis process of glass material, but also accordingly increase the production cost. Interestingly, some reducing agents such as Si 3 N 4 and SiC that exhibit intrinsic reduction nature, have been utilized to synthesize certain transparent and colorless glasses activated with cerium ions. This strategy seems to be more effective in borosilicate, borogermanate, and borate glass systems as reported in our previous work.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some reducing agents such as Si 3 N 4 and SiC that exhibit intrinsic reduction nature, have been utilized to synthesize certain transparent and colorless glasses activated with cerium ions. This strategy seems to be more effective in borosilicate, borogermanate, and borate glass systems as reported in our previous work. It is experimentally confirmed that Ce 4+ is easier to be reduced in borosilicate glass containing Al 2 O 3 component by introducing nitrides such as Si 3 N 4 in previous work .…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2(a), two groups of broad bands in 250-300 and 300-400 nm regions are ascribed to the 4f-5d 3,4,5 and 4f-5d 1,2 transition, respectively [18]. Under direct excitation at the 4f-5d 1,2 , a typical emission 5d 1 -2 F 5/2,7/2 Ce 3+ emission extending from 300 to 450 nm is observed, as shown in the emission spectra of Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Optical transmittance spectra [18,19]. Generally, the higher the concentration of Ce 3+ ions in glass, the shorter wavelength the cut-off edge of glass will be.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation